Some Studies on Gamma Irradiated Brown Sarson - Kumar, P R; Das, K (Annals of Arid Zone, 2016)
Dry seeds of cultivar brown sarson irradiated with gamma rays ( 5,000r to 40,000r) germinated uniformly, but the survival rate of mature plants decreased with the increased dosages. The effects on plant height, number of braches, different fruit characters. pollen and ovule sterility was not significant but indicated the possibility of directing selection in MI generation. Higher dosages of irradiation caused increased pollen sterility. Higher pollen sterile plants showed multivalents at metaphase I and irregular distribution of chromosomes at anaphase-I.